Community-Based Security Systems and Technology at the Madura 24-Hour Store in Yogyakarta: A Legal Protection Perspective - Hotibul Umam; Imam Hakiki (Education of Law Journal, 2026)
Madura 24-hour convenience stores in the Special Region of Yogyakarta face high security risks due to the potential for nighttime crime, which often cannot be immediately addressed by formal legal protections. These conditions have prompted business owners to establish alternative security mechanisms. This study aims to analyze community- and technology-based security systems at 24-hour Madura stores in Yogyakarta from a legal protection perspective. Using qualitative methods through an empirical legal approach and normative evaluation, data were collected via semi-structured interviews with store owners or attendants in the Babarsari and Pogung areas of Sleman Regency, as well as through document analysis. The results show that the effectiveness of self-regulated legal protection is achieved through the integration of technology and social control. In Babarsari, preventive legal protection is realized through the use of CCTV as digital evidence combined with local wisdom. Meanwhile, in Pogung, protection relies on direct surveillance and community social capital. Madura kinship networks and family associations function as informal legal institutions that establish a system of collective oversight. This study concludes that, from a legal perspective, the existence of 24-hour Madura grocery stores relies not only on repressive legal protection provided by law enforcement, but also on a self-reliant legal protection framework that responsively integrates technology and local wisdom.